1995
DOI: 10.1128/jvi.69.5.3201-3205.1995
|View full text |Cite
|
Sign up to set email alerts
|

Bovine papillomavirus E1 protein can, by itself, efficiently drive multiple rounds of DNA synthesis in vitro

Abstract: Bovine papillomavirus E1 protein was found to be as efficient as the simian virus 40 large T antigen in initiating DNA synthesis in a cell-free system derived from COS1 cells. Multiple rounds of DNA synthesis occur, initiated at the bovine papillomavirus type 1 origin. Therefore, E1 functions in vitro as a lytic virus initiator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
2
20
0
2
Order By: Relevance
“…Thus, a BPV-1 replicon can replicate in cells in the absence of E2TA when sufficient wild-type E1 protein is present. This result is consistent with that seen when the E1 gene of HPV-1 is overexpressed in similar transient replication assays in tissue culture cells (11) and correlates with the dispensability of E2TA in in vitro BPV-1 DNA replication assays (3,27,37,47). When efficiently expressed in trans from the CMV immediate-early promoter, several of the E1 mutants (R370T, F542V, L466H, and D497A/G498A) that did not support replication in the context of the full-length viral genome could support replication in C33A cells (Fig.…”
Section: Resultssupporting
confidence: 88%
“…Thus, a BPV-1 replicon can replicate in cells in the absence of E2TA when sufficient wild-type E1 protein is present. This result is consistent with that seen when the E1 gene of HPV-1 is overexpressed in similar transient replication assays in tissue culture cells (11) and correlates with the dispensability of E2TA in in vitro BPV-1 DNA replication assays (3,27,37,47). When efficiently expressed in trans from the CMV immediate-early promoter, several of the E1 mutants (R370T, F542V, L466H, and D497A/G498A) that did not support replication in the context of the full-length viral genome could support replication in C33A cells (Fig.…”
Section: Resultssupporting
confidence: 88%
“…A similar, if not identical, set of cellular replication factors and enzymes, in addition to viral initiator proteins, is utilized by SV40 (Tsurimoto et al, 1990;Weinberg et al, 1990) and bovine papillomavirus-1 (Muller et al, 1994) at the origin of replication to initiate DNA synthesis. Analysis of the essential cis sequences shows that the BPV-1 minimal origin (MO) (Ustav et al, 1993) resembles a typical eukaryotic origin of replication (DePamphilis, 1993) and it has been suggested that this similarity could also be extended to the mechanisms of replication of all papovaviruses (Nallaseth and DePamphilis, 1994;Bonne-Andrea et al, 1995). However, the ability of the papillomaviruses to be stably maintained as plasmids distinguishes them from other papovaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…The bovine papillomavirus type 1 (BPV-1) E1 protein is an essential viral DNA replication factor that is both an origin recognition protein (5,6,13,17,18,20) and an ATP-dependent helicase (14,21). E1 binds to an 18-bp inverted repeat element (5) and presumably initiates DNA replication both by unwinding the origin duplex DNA and by recruiting cellular replication factors such as DNA polymerase ␣ (3,11) to the initiation complex. In vitro, E1 alone is sufficient to initiate replication (3), but in vivo the viral full-length E2 transcriptional activator protein is also absolutely required (16).…”
mentioning
confidence: 99%
“…E1 binds to an 18-bp inverted repeat element (5) and presumably initiates DNA replication both by unwinding the origin duplex DNA and by recruiting cellular replication factors such as DNA polymerase ␣ (3,11) to the initiation complex. In vitro, E1 alone is sufficient to initiate replication (3), but in vivo the viral full-length E2 transcriptional activator protein is also absolutely required (16). E1 can form complexes with the E2 protein (2,8,15,20), and both binding to and unwinding of origin DNA by E1 is enhanced by these cooperative interactions with E2 (4,9,13,20).…”
mentioning
confidence: 99%